IMPROVING THE QUALITY OF EDUCATION THROUGH SYSTEMATIC MANAGEMENT - Zubaidi, Zubaidi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Improving the quality of education is an urgent need in facing the dynamic development of the world of education. One approach that can be used to achieve this goal is through systematic management. This research aims to investigate how the implementation of systematic management can improve the quality of education at Nurul Barokah Vocational School. The research method used is action research, involving active participation from education stakeholders at Nurul Barokah Vocational School. Data was collected through observation, interviews and document analysis, then analyzed using a qualitative approach. The research results show that the implementation of systematic management is able to make a positive contribution to improving the quality of education at Nurul Barokah Vocational School. Improvements were found in the teaching, learning, evaluation and resource management processes. Management systematization provides a clear framework, enables quick identification of problems, and provides a basis for better decision making.